A functional balance profile of school aged children and adolescents diagnosed with Down Syndrome, schooled in the Eastern Cape province of South Africa: a pilot study. - Nolte, Cilje (Department of Health and Rehabilitation Sciences, 2026)
Children and adolescents with Down Syndrome (DS) are at a higher risk of falls due to impaired balance and gait patterns, which complicates their ability to safely engage in daily activities (Jung, Chung & Lee, 2017). Assessing balance function in children is not only important for identifying balance deficits, but also to inform and highlight integral areas of balance function that should be addressed during rehabilitation. Although various outcome measures have demonstrated acceptable reliability and validity in typically developing children, the applicability of outcome measures in children with DS has not been fully established. This pilot study aimed to evaluate the clinimetric properties, including reliability, validity, and practicality, of four functional balance outcome measures: the Paediatric Balance Scale (PBS), the second edition of the Bruininks-Oseretsky Test of Motor Proficiency (BOT-2, Subtest 5), the full Children's Balance Evaluation Systems Test (Kids- BESTest), and its shortened version (Kids Mini-BESTest). To contextualise the results, a control group of age- and sex-matched typically developing peers was included for comparison. The primary objectives were to assess reliability (inter-rater and test-retest), known-groups validity, criterion validity (via correlations with Timed Up & Go (TUG) scores), and internal consistency (using Cronbach's alpha) of each measure. Outcome measures used in real-world settings like schools and clinics require qualities beyond being clinimetrially sound. Aspects regarding the practical applicability of these outcome measures should also be considered. Thus, this study evaluated the accessibility, safety, and practicality of administering these tests in a DS population, including time requirements, cost-effectiveness, and participant acceptability. The secondary objectives were to describe the balance profile of the DS group and explore the effects of potential confounders, including middle ear function, cochlear outer hair cell function, and Body Mass Index (BMI), on balance performance and test outcomes. Children from the Merryvale School for Special Education in Gqeberha, Eastern Cape (EC), South Africa (SA), participated in this study, while typically developing controls were sourced from local schools in the same area. Safety measures, such as gait belts and close guarding, were implemented to ensure participant safety and minimise fall risk during assessments. Data confidentiality and participant welfare were prioritised throughout the study. The results demonstrated significant differences in balance performance between children with DS and typically developing peers across all four assessment tools. The DS group exhibited lower mean scores and shorter durations for balance tasks, with notable floor effects in specific items, particularly within the Kids-BESTest and PBS. Independent t-tests revealed statistically significant group differences (p < 0.001), with large effect sizes (e.g., Cohen's d = 3.94 for BOT-2 Subtest 5). Reliability analysis showed good inter-rater and test-retest reliability for all tools, with Cronbach's alpha values ranging from 0.867 to 0.971, indicating strong internal consistency. Validity testing confirmed known-groups validity, with balance assessments effectively differentiating between DS and typically developing groups, while criterion validity demonstrated a significant association between balance test scores and TUG performance (e.g., Kids-BESTest R² = 0.536, p < 0.001). Health-related variables, such as BMI and middle ear status, significantly correlated with poorer balance outcomes. This correlation further emphasises the multifactorial nature of balance impairments in children with DS. This study offers initial insights into effective, safe balance assessment methods which audiologists can use for DS populations. These insights ultimately pave the way for future research to support balance related interventions.